Can we improve how we screen applicants for initial teacher education?. (January 2020) - Klassen, Robert M.; Kim, Lisa E.; Rushby, Jade V.; Bardach, Lisa
Abstract: Identifying the best possible candidates for initial teacher education (ITE) programs is one of the first steps in building a strong teacher workforce. We report three phases of development and testing of a contextualized teaching-focused situational judgment test (SJT) designed to screen applicants at a large and competitive ITE program in the U.K. Results showed that the SJT was a reliable and predictive tool that enhanced existing screening methods. We suggest that using state-of-the art methods to help make admissions decisions could improve the reliability, validity, and fairness of selection into ITE. Highlights: A test for screening applicants to teacher education was developed. Internal consistency of the test was acceptable. The test was significantly correlated with interview performance. The test was more predictive of interview performance than current screening methods. High scorers on the test performed better at interview than low scorers.